Preliminary testing by adults of a haptics-assisted robot platform designed for children with physical impairments to access play. Issue 5 (20th October 2018) - Sakamaki, Isao; Adams, Kim; Medina, Maria Fernanda Gomez; Cruz, Javier Leonardo Castellanos; Jafari, Nooshin; Tavakoli, Mahdi; Janz, Heidi
ABSTRACT: Development of children's cognitive and perceptual skills depends heavily on object exploration and experience in their physical world. For children who have severe physical impairments, one of the biggest concerns is the loss of opportunities for meaningful play with objects, including physical contact and manipulation. Assistive robots can enable children to perform object manipulation through the control of simple interfaces. Touch sensations conveyed through haptic interfaces in the form of force reflection or force assistance can help a child to sense the environment and to control a robot. A robotic system with forbidden region virtual fixtures (VFs) was tested in an object sorting task. Three sorting tasks—by color, by shape, and by both color and shape—were performed by 10 adults without disability and one adult with cerebral palsy. Tasks performed with VFs were accomplished faster than tasks performed without VFs, and deviations of the motion area were smaller with VFs than without VFs. For the participant with physical impairments, two out of three tasks were slower with the VFs. This implies that forbidden region VFs are not always able to improve user task performance. Alignment with an individual's unique motion characteristics can improve VF assistance.